Analisis Risiko Cacat dan Biaya Kegagalan Produk Bak Mandi dan Pot Teraso - Ovika Agustin Anugrah Niawan; Herlina Herlina (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
UD. Nuraji Pot is a trading company that produces bathtubs and terrazzo pots that still experience product defects, causing company losses. This study aims to analyze the root causes of product defects using Root Cause Analysis (RCA), determine the level of failure risk using Failure Mode and Effect Analysis (FMEA), calculate the cost of failure using Cost of Quality (COQ), and launch the implementation of improvements in the production process. Data were obtained through observation, interviews, and data documentation for the production period July–December 2025. The results showed that the types of defects that occurred included fine cracks, breaks during shipping, and uneven coating. The results of the FMEA analysis showed that fine cracks in the drying and mold release process had the highest Risk Priority Number (RPN) value of 504. The total cost of failure before repair was Rp. 186,839,412.00. The implementation of improvements succeeded in reducing the percentage of defects from 2.32% to 1.39% and reducing the cost of failure by 37.54%.